Application of spreadsheet-based carbon footprint tool "TransCO2" in estimating carbon dioxide emissions of a fuel switch project conversion of jeepneys to Auto-LPG - Ramos, John Michael E.
Road transport including private cars, jeepneys, trucks and buses emits local pollutants (CO, NOx, HC and PM) and greenhouse gas (GHG) emissions such as CO2, which contribute to air pollution and climate change. The proposed LPG Jeepney Conversion project is one of the possible strategies to reduce the GHG emission of the transportation sector. This study is conducted to apply the carbon footprint tool TransC02 on accounting the CO2 emissions of baseline and project scenarios in 94 traffic zones of Metro Manila for year 2015-2020. The tool is updated and customized to adapt to local conditions. Fuel efficiency profiles (FEPs) of the following vehicle types are developed and incorporated into the tool: passenger car (gas); passenger car (diesel); utility vehicle (gas); utility vehicle (diesel); motorcycle (gas); truck (diesel); taxi (gas); taxi (LPG); jeepney (diesel); jeepney (LPG); AUV (diesel); bus (diesel); bus (CNG); tricycle 2-stroke (gas); and tricycle 4-stroke (gas). The CO2 emissions resulting from TransC02 are compared with the IES Philippines (Manila Observatory, 2004) study emissions and manual calculation as well. The total emission for the baseline scenario in 2015 was estimated at 33,706 tons per day or 12,304 kilotons for the whole year, which is about 34% lower than the total for the 2015 baseline scenario estimated from IES Philippines study. The difference in the estimates is due to the 4 adjacent provinces included in the BAU scenario of IES Philippines study, the variation of method used in estimation of CO2 emissions, share of vehicle-kilometers and the emission factors of vehicles. The total CO2 emissions for the project scenario in 2020 were estimated at 34,792 tons per day which is an increase of 51 tons per day or 0.15% increase relative to the baseline. The LPG Jeepney Conversion project will lead to higher C02 emissions due to lower fuel efficiency of Auto-LPG jeepneys.